Crash! Bang! Boo! - McGee, Joe 1972-; Long, Ethan (New York : Aladdin, 2019)
Vamprya, Franky, and Wolfy fix the mess Igor Jr. caused at Dr. Frankensteins lab while Baron Von Grump plots to sabotage The Villages 150th anniversary celebration by shutting off the power.
Keywords: Monsters -- Juvenile fiction; Scouting (Youth activity) -- Juvenile fiction